FORMATION COGNITIVE FLEXIBILITY AS A BASIC COMPETENCE OF A FUTURE TEACHER: SCIENTIFIC AND THEORETICAL SUBSTANTIATION THIS PROBLEM - Savchuk, Borys; Romanyshyn, Ruslana; Khimchuk, Liliana; Vysochan, Lesia (Mountain School of Ukrainian Carpaty, 2021)
In the article, in line with the discourse of foreign and Ukrainian scientists, a scientific and theoretical substantiation the problem of forming cognitive flexibility as a professional competence future teachers is made. It is shown that cognitive flexibility is studied in psychology, philosophy, clinical medicine, management, pedagogy, cybernetics and other fields of knowledge. The content of the formed beginning of the XXI century is revealed. theory of cognitive flexibility. Its representatives criticize the "traditional" model of education as "linear", because the information in it is presented in a logical, consistent structured form. Therefore, it does not meet modern social challenges and the needs of training a modern specialist who must quickly adapt to new requirements of pedagogical activity. The essence of professional competence of the future teacher, its main structural components and pedagogical conditions of realization are found out.Four main components of cognitive flexibility as a professional competence future teachers are identified and characterized: 1) cognitive abilities (possession of psychophysiological and receptive abilities and abilities for adequate understanding of modern social and educational challenges); 2) adaptive abilities (quick adaptation to different life circumstances); 3) flexibility of thinking (adequate response to changes in the professional and social environment); 4) emotional flexibility in the "narrow" sense (value-emotional perception of the realities of professional and social life; tolerant response to specific behaviors of students, colleagues).